The Authority of Local Governments in Determining Parking Retribution Rates - Lubis, Fahmi Sahil; Rizal, Muhammad (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The imposition of parking retribution fees represents one of the local government's authorities in managing Regional Original Income (PAD). In the City of Medan, the parking retribution policy plays a strategic role in both service management and local fiscal policy.Purposes of the Research: This study aims to analyze the authority of the Medan City Government in setting parking retribution rates and to evaluate the legal basis and implementation of such authority.Methods of the Research: The research applies a normative and empirical juridical approach by using document analysis and interviews with the Medan City Transportation Department and local parking users.Results Main Findings of the Research: The authority to determine parking retribution rates is regulated under Law Number 28 of 2009 concerning Regional Taxes and Levies and further stipulated through Medan City Regional Regulations. However, implementation issues arise due to weak socialization, rate inconsistencies, and insufficient supervision, leading to potential revenue leakage.